Navegando pela cultura: identidade e memória de uma moradora do rio Anequara - SILVA, Manuelle Pereira da (2022)
This work discusses Culture, Identity and Memory through the narratives of a riverside woman on the Anequara River. Therefore, the research aims to discuss the culture, identity and memory of the riverside community from Anequara River, from the point of view of one of the oldest residents. As a theoretical framework, the authors used were Teixeira (2015) and Candau (2014) to talk about identity and its relationship with memory. Leal (2011) and Halbwachs (2006), making notes on culture and memory. Netto and Ramos (2000) who deal with the link between identity and culture. Maciel (2021) and Moita Lopes (2001) consider oral narratives in line with the concept of memory, culture and identity. And, Pereira, Cardoso and Pantoja (2006), who present how the Anequara River is constituted. As a methodology, a field research was used, carried out through an interview, which was recorded, transcribed and later analyzed. The results show that a transformation is taking place in the way residents perceive many aspects of value. The elderly woman's memories provide a sense of what life was like in the past compared to the present. It is concluded that the elderly has in her memories, memories acquired from their experiences and interpersonal relationships, in addition, the community undergoes changes in cultural and identity aspects.